The shock of the old : technology and global history since 1900 / David Edgerton. - Edgerton, David (Profile Books, 2019)
'Shock of the Old' forces us to reassess the significance of old inventions such as corrugated iron and sewing machines and rethink the relative importance we place on the invention of something new, its application, and its widespread adoption. It challenges the idea that we live in an era of ever increasing change and, interweaving political, economic and cultural history, teaches us to think critically about technology.